Analisis Metakognisi Siswa pada Proses Penalaran Matematis dalam Menyelesaikan Soal - Nuranny Novagusliana (Departement of Mathematics Education, 2024)
This research aims to analyze the metacognitive abilities of vocational school students in the mathematical reasoning process in solving problems. The subjects of this research were 30 class X students at SMK PGRI 1 Sumedang. The research object used is students' metacognitive abilities in mathematical reasoning. The research method used is quantitative. The results of the research show that students' metacognitive abilities are at a low level, namely tacit use, where students are less aware of their abilities, weaknesses when solving problems, and do not apply strategies in solving problems without certain awareness and are careless in answering problem solving without paying attention to the correctness of the answer.